Facile fabrication of triboelectric nanogenerator based on low-cost thermoplastic polymeric fabrics for large-area energy harvesting and self-powered sensing. (November 2019) - Peng, Fei; Liu, Di; Zhao, Wei; Zheng, Guoqiang; Ji, Youxin; Dai, Kun; Mi, Liwei; Zhang, Dianbo; Liu, Chuntai; Shen, Changyu
Abstract: Triboelectric nanogenerator (TENG) which can work as novel power provider and self-powered sensor has been in rapid development in recent years. Unfortunately, fabricating large-area TENG through a low-cost, facile, continuous and environmentally friendly method still remains a challenge but highly desired. Herein, via melt blowing technique, a low-cost, durable and large-area fabric-based triboelectric nanogenerator (FB-TENG) was fabricated. Such FB-TENG comprises of polypropylene non-woven fabrics (PP-NWF), commercial polyamide 66 fabrics (PA-66-F) and conductive fabrics (Ni@fabrics). Furthermore, it has remarkable stability even when working for a long time, showing multifunctional applications. For example, on the one hand, as a power provider, FB-TENG can drive miniature electronic products. On the other hand, as a self-powered sensor with extremely short response time, FB-TENG can collect pedestrian volume and monitor pugilism training precisely. This work paves a new way for developing FB-TENG through a low-cost, facile, continuous and environmentally friendly method, showing potential applications including self-powered motion tracking, tactile sensing and remote wireless training monitoring system. Graphical abstract: Via melt blowing technique, large-area triboelectric layers with enhanced contact intamacy were fabricated. A low-cost, durable and large-area fabric-based triboelectric nanogenerator (FB-TENG) was assembled. Moreover, apart from power provider, owing to its fast response in the form of electric signal, such FB-TENG can serve as self-powered sensor with the ability of wireless display. Image 1 Highlights: Commercial but low-cost plastics were selected to serve as triboelectric layers. Via melt blowing technique, large-area triboelectric layers were fabricated. Low-cost, durable and large-area fabric-based TENG (FB-TENG) was assembled. Such FB-TENG can work as self-powered sensor with the ability of wireless display. Such FB-TENG possesses fast response in the form of electric signal.